Restoration of degraded peat swamp forest through community participation: the case of Raja Musa Forest Reserve, North Selangor, Malaysia - Alam, Md Jahangir (2023)
Peat swamp forest (PSF) is an ecosystem of global significance. It sequesters and stores atmospheric carbon, regulate hydrological system, provide habitat for many endemic wildlife, and deliver livelihoods support to thousands of local people. Despite these values, during the last several decades PSF have been subject to extensive deforestation and degradation globally. A significant portion (7%) of the Malaysia’s total land mass is PSF that are traditionally managed with the state governance system. However, depletion of this PSF has been continued due to various anthropological causes including intensive logging, drainage, fire, conversion to agriculture, oil pam, settlement, industry etc. Continued depletion of PSF with the centralized governance system (in other ways, here, state forest management, SFM system), and the success of community-based forest management (CBFM) approach in many countries of the world motivated several South-East Asian (SEA) countries to impart changes in their governance system from traditional centralized/state governance approach to CBFM approach. Recently, in Malaysia, specifically State Government of Selangor introduced CBFM approach in the governance of depleted PSF at Raja Musa Forest Reserve (RMFR) in collaboration with Global Environment Centre (GEC, a national non-government organisation). However, the success and/or failure of the newly applied CBFM approach in terms of PSF restoration and community development has not been fully explored yet. The aim of this research was to understand the effectiveness of community participation toward restoration and sustainable conservation of degraded PSF of RMFR in Peninsular Malaysia, with the following objectives: (i) ascertain characteristics of peat, peatland and peat swamp forest, and activities involve in PSF restoration through literature review, (ii) examine the formation and functions of social capital, and the level of community participation in PSF restoration, (iii) analyse the impacts of institutional setting and governance on sustainable conservation and community-based PSF restoration, (iv) assess ecological outcomes of community-based PSF restoration programme, and (v) examine the effect of management regimes of the PSF on local peoples’ socio-economic and environmental benefits. To attain these objectives, the study deployed a pluralistic research approach of social research and ecological (e. g. vegetation survey) study. For social research, both qualitative and quantitative data were collected through a stakeholders’ workshop (with the presence of 49 participants from federal and state Forestry Department, other government agencies, NGOs, local government, academics, local community leaders), four focus group discussions, five key informant interviews and 200 household interviews in four adjacent villages of RMFR. In addition, secondary data was collected from official documents of GEC local office.